Gelastic Epilepsy and Hypothalamic Hamartoma - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Three patients with hypothalamic hamartoma and gelastic seizures were studied using ictal single-photon emission computed tomography and EEG recordings with depth electrodes at the University of Alabama at Birmingham Epilepsy Center.